Ethnic concentration and extreme right-wing voting behavior in West Germany - Verena Dill (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Using data from the German Socio-Economic Panel (SOEP) and administrative data from 1996 to 2009, I investigate the question whether or not right-wing extremism of German residents is affected by the ethnic concentration of foreigners living in the same residential area. My results show a positive but insignificant relationship between ethnic concentration at county level and the probability of extreme right-wing voting behavior for West Germany. However, due to potential endogeneity issues, I additionally instrument the share of foreigners in a county with the share of foreigners in each federal state (following an approach of Dustmann/Preston 2001). I find evidence for the interethnic contact theory, predicting a negative relationship between foreigners' share and right-wing voting. Moreover, I analyze the moderating role of education and the influence of cultural traits on this relationship.
Keywords: D72; R23; J15; 330; ethnic concentration; extreme right-wing voting; group threat; interethnic contact